Forging family outdoor identity: natural conversations about the effect of outdoor experiences on attitudes toward environmental science - Crockett, Michele, author; Champ, Joseph, advisor; Long, Marilee, advisor; Bright, Alan, committee member (Colorado State University. Libraries, 2013)
This study used a qualitative, "walking interview" method to explore how families' outdoor experiences and parent-child interactions affected their attitudes about environmental science. Members of six families--at least one parent and one child--were interviewed during a walk in a city-maintained natural area in Fort Collins, Colorado. The discussion examined the themes of family time spent outdoors, engagement in science topics at school, family discussions about environmental science, and family media use. The conversational data was analyzed using idiographic and nomothetic approaches, from which emerged the theme of family outdoor identity-the extent to which families perceive themselves as outdoor-oriented. Parents in the study exhibited varying degrees of guiding behavior in discussions about environmental science, regardless of whether one of the parents had a science background. Although this study indicated that young children in particular consume very little print media, older children use electronic media, particularly web-based search tools, to find information about environmental topics. In addition, social media emerged as a useful media tool for parents seeking information about environmental topics.